The Relationship between Entrepreneurial Alertness and Interfamilial Succession: The Analysis of Questionnaire Survey of Small and Medium-sized Enterprises in Kita-Kanto region - Nao YAMAUCHI; Takeyasu ICHIKOHJI; Hidenori SATO (AAOS Transactions)
This study examined how the Entrepreneurial Alertness (EA) of Small and Medium-sized Enterprises (SMEs) managers affected strategic decision-making efforts and firm performance under COVID-19 pandemic situation. This study simultaneously focused on the managers’ interfamilial successor characteristic to study antecedents of EA which have been calling for further clarifications in empirical research. The data was taken from a questionnaire survey for SMEs in Kita-Kanto region and examined by Structural Equation Modeling. The results showed positive relationship among EA, firm performance, and strategic decision-making efforts. On the other hand, the interfamilial successor characteristic was found to have negative impact on EA. The findings from this study contributed to both academic and managerial fields. For academic field, our results would lead to further elucidation of EA antecedents. For managerial field, there are multiple implications for SMEs struggling to secure and train next generation’s manager with EA.